Balinese Convergence and Divergence in Sasak Community - Saputra, I Gede Widya (Universitas Pendidikan Ganesha, 2012)
The aim of this study was to find out what factors which make Balinese do convergence and divergence in Sasak community. Convergence and divergence are parts of Accommodation Theory. Accommodation Theory was developed by Giles and his colleagues. Accommodation Theory is also known as Communicative Accommodation Theory (CAT). CAT deals with linguistic variation, more specifically, with the results of adjustments and accommodations made by the speakers during the communication process. The study is a descriptive study. The researcher conducted the research in West Lombok Regency. There are several places that are visited by the researcher in conducting this research, such as Traditional Market, Senior High School, and Noble Sasak Environment. The data of this research were obtained from those places. After obtaining the data from the conversations among Balinese and Sasak in those places, the researcher than classified the speech obtained into convergence conversation and divergence conversation. Finally, the result of this study shows that Balinese do convergence in order to intimate their relationship, to maintain equality in terms of profession, to win social approval, and to avoid conflict. Meanwhile, the result of this study also shows that Balinese do divergence in order to maintain a positive social identity, to keep intimacy among Balinese and Balinese, to show superiority.